2021
DOI: 10.1242/dmm.049029
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing STAT3 activity protects the endothelial barrier from VEGF-mediated vascular permeability

Abstract: Vascular permeability triggered by inflammation or ischemia promotes edema, exacerbates disease progression, and impairs tissue recovery. Vascular endothelial growth factor (VEGF) is a potent inducer of vascular permeability. VEGF plays an integral role in regulating vascular barrier function physiologically and in pathologies, including cancer, stroke, cardiovascular disease, retinal conditions, and COVID-19-associated pulmonary edema, sepsis, and acute lung injury. Understanding temporal molecular regulation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 89 publications
(139 reference statements)
0
20
0
Order By: Relevance
“…In addition to apoptosis and DNA damage, previous studies showed that high amounts of NO ( 65 ), VEGF ( 66 ), and MPO ( 67 ) could be synthesized and released in cells in response to ROS and inflammation stimuli. All the enhanced NO ( 68 ), VEGF ( 69 ), and MPO ( 70 ) could mediate an increase in the permeability of vascular endothelium, which may result in the leakage of plasma albumin to tissues and cause hypoxia and edema of organs, ultimately triggering the function dysfunction and exacerbating the disease progression. Thus, NO, VEGF, and MPO were also therapeutic targets to prevent and treat nanomaterial-induced organ injuries.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to apoptosis and DNA damage, previous studies showed that high amounts of NO ( 65 ), VEGF ( 66 ), and MPO ( 67 ) could be synthesized and released in cells in response to ROS and inflammation stimuli. All the enhanced NO ( 68 ), VEGF ( 69 ), and MPO ( 70 ) could mediate an increase in the permeability of vascular endothelium, which may result in the leakage of plasma albumin to tissues and cause hypoxia and edema of organs, ultimately triggering the function dysfunction and exacerbating the disease progression. Thus, NO, VEGF, and MPO were also therapeutic targets to prevent and treat nanomaterial-induced organ injuries.…”
Section: Discussionmentioning
confidence: 99%
“…In the pathway analysis, we found that laminarin’s targets played a role in many cell signaling pathways related to COVID-19 and cervical carcinoma. The VEGF signaling pathway plays a vital role in the pathologies of COVID-19-associated pulmonary edema, sepsis, and acute lung injury ( Wang et al, 2021 ). A clinical comparison study among the COVID-19 patient categories found a significantly lower level of VEGF in the mildly symptomatic patients ( Tripathy et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The concept of molecular bridging is proposed to promote neovascularization and alleviate lower limb ischemia by promoting angiogenesis through angiogenic growth factors [1,2]. However, the perfusion pressure of neovessels could not be maintained due to the poor maturity and strong leaky effect on the exogenous gene therapy [3,4]. The previous results showed the transcription factor made from the ZFP can combine with the endogenous VEGF promoter to stimulate VEGF-A family and splice variants(such as121,145,165,189,206)expression in the Hy926 cell experiments [5].…”
Section: Introductionmentioning
confidence: 99%